Correlation of PET-CT, MRI and histopathology findings in the follow-up of patients with nasopharyngeal cancer - Ak,Semih (2021)
Abstract Introduction: Surgical treatment options are limited for nasopharyngeal cancer for many reasons including epidemiological and histological properties, proximity to important structures, heavy lymphatic drainage, and the difficulty in ensuring a safe surgical margin; therefore primary treatment is generally radiotherapy and chemotherapy. With current radiotherapy technology, oncological success has been increased and the quality of life of patients during the postradiotherapy period is improved. Objective: The role of magnetic resonance imaging and positron emission-computed tomography in the follow-up of recurrent nasopharyngeal cancer patients who were initially treated with radiotherapy was evaluated with respect to histopathological findings. Methods: A total of 110 patients with nasopharyngeal cancer who had received radiotherapy were included in the study. Patients who were suspected to have recurrence according to endoscopic nasopharyngeal examination and magnetic resonance imaging findings were requested to undergo positron emission-computed tomography. Biopsies were taken from 40 patients who had suspicious lesions in positron emission-computed tomography images. These patients’ age, gender, presence/absence of contrast enhancement on magnetic resonance imaging, the SuvMax values of nasopharyngeal and neck lesions, T/N phases at initial diagnosis, histopathological recurrence, and history of neck dissection were assessed. Results: Recurrence was observed in 8 patients (20.0%). Among these, 4 (10.0%) had recurrence at the nasopharynx and 4 (10.0%) at the neck. Patients with recurrence were found to be of older age, male gender, advanced T/N phase, contrast enhancement on magnetic resonance imaging, and higher nasopharyngeal and neck SuvMax values in positron emission-computed tomography. However, these differences were not statistically significant. Only the history of neck dissection was significantly more common among those with recurrence (p < 0.001). However, in multivariate analysis, those with a nasopharyngeal SuvMax value higher than 4.58 were found to have 7.667-fold higher risk for recurrence (p = 0.036). Conclusions: Magnetic resonance imaging and positron emission-computed tomography should be evaluated together in the follow-up of nasopharyngeal cancer. Patients with minimal SuvMax 4.58 on positron emission-computed tomography after contrast enhancement in the T2 sequence on magnetic resonance imaging may considered appropriate for biopsy. Biopsies in patients with a SuvMax value lower than 4.58 can be avoided. Thus, patients avoid surgical stress and unnecessary costs.